Motion sickness whilst reading as a passenger in the car is highly predictive of vestibular migraine - Rova, Konstantina; Joffily, Lucia; Carvalho, Lara; Cortese, Elvira; Koohi, Nehzat; Kaski, Diego (Frontiers in Neurology, 2024)
Background: Vestibular Migraine (VM) affects up to 2.7% of the general population. Despite the establishment of diagnostic criteria by the Bárány Society and its inclusion in the International Classification of Headache Disorders, the clinical diagnosis of VM remains challenging due to its complex pathophysiology and symptom overlap with other dizziness disorders. Motion sickness is a core feature of migraine and can be interrogated through simple questionnaires.Objective: This study aims to identify to what extent motion sensitivity can predict VM compared to other causes of dizziness.Methods: We conducted a cross-sectional study involving 113 patients from the vestibular neurology clinics at University College London Hospitals. Participants were categorised into VM, Persistent Postural Perceptual Dizziness (PPPD), combined VM and PPPD, and 'other' dizziness etiologies. Data on motion sickness history and dizziness during car travel were collected through structured interviews and analysed using logistic regression to assess the predictive value of these symptoms for VM.Results: A substantial portion of patients with VM (91.2%) reported nausea or dizziness when reading as a passenger, a symptom significantly more prevalent than in those with PPPD or other dizziness diagnoses. Logistic regression indicated that VM patients are significantly more likely to experience these symptoms compared to non-VM patients, with an odds ratio suggesting a strong predictive value for this symptom in diagnosing VM.The findings highlight increased motion sensitivity while reading in a moving vehicle as a promising diagnostic tool for VM, offering a practical aid in clinical settings to distinguish VM from other vestibular disorders.